2016
DOI: 10.3892/etm.2016.4007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory analysis of late-onset glutaric aciduria type I (GA-I) in Uighur: A report of two cases

Abstract: The aim of the present study was to investigate the clinical, biochemical and genetic mutation characteristics of two cases of late-onset glutaric aciduria type I (GA-I) in Uighur. The clinical data and glutaryl-CoA dehydrogenase (GCDH) genetic test results of two cases of late-onset GA-I in Uighur were collected and analyzed, and reviewed with relevant literature. One patient with late-onset GA-I primarily exhibited clinical intermittent headache, while the other patient was asymptomatic. The urinary organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Recent clinical studies confirmed the previously demonstrated in vitro and in vivo evidence of neurotoxicity, induced by glutaryl‐CoA, GA, and 3‐OH‐GA as well as altered glutarylation patterns of mitochondrial proteins, 13 thus extending this concept toward long‐term neurotoxicity 14 . The cumulative neurotoxicity can be supported by the observation that extrastriatal disease manifestations are more often or even exclusively found in the HE group 14–20 . Accordingly, individuals of the HE group are more often confronted with extrastriatal MRI changes, 14 particularly in the periventricular white matter in combination with progressive neuroaxonal compromise and concomitant cerebral GA accumulation 21,22 .…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recent clinical studies confirmed the previously demonstrated in vitro and in vivo evidence of neurotoxicity, induced by glutaryl‐CoA, GA, and 3‐OH‐GA as well as altered glutarylation patterns of mitochondrial proteins, 13 thus extending this concept toward long‐term neurotoxicity 14 . The cumulative neurotoxicity can be supported by the observation that extrastriatal disease manifestations are more often or even exclusively found in the HE group 14–20 . Accordingly, individuals of the HE group are more often confronted with extrastriatal MRI changes, 14 particularly in the periventricular white matter in combination with progressive neuroaxonal compromise and concomitant cerebral GA accumulation 21,22 .…”
Section: Introductionsupporting
confidence: 57%
“…14 The cumulative neurotoxicity can be supported by the observation that extrastriatal disease manifestations are more often or even exclusively found in the HE group. [14][15][16][17][18][19][20] Accordingly, individuals of the HE group are more often confronted with extrastriatal MRI changes, 14 particularly in the periventricular white matter in combination with progressive neuroaxonal compromise and concomitant cerebral GA accumulation. 21,22 Clinically, the HE group has a higher risk of cognitive dysfunction, 23 subdural hematoma, 24 and larger head circumferences 25 compared to the LE group.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature search was performed by the authors and conducted in PubMed for publications between January 2000 up to May 2022, that report GCDH variants in GA1 patients. For this search the following MeSH terms were used: “glutaric aciduria type 1,” “glutaric acidemia type 1,” “glutaric aciduria type I,” “glutaric acidemia type I,” “glutaryl‐CoA dehydrogenase deficiency,” and “GCDH” 30–107 . References from selected articles from before the year 2000 with complete description of GA1 patients were also included.…”
Section: Methodsmentioning
confidence: 99%
“…Beside macrocephaly, suggestive clinical signs comprise acute neurologic manifestations (e.g. occurring during febrile illness or other catabolic states) like acute or chronic onset of MD in infants, gait abnormalities or (truncal) muscular hypotonia 5,45,88–97 . Individuals with late‐onset form may present with unspecific neurologic signs like polyneuropathy, incontinence, headache, early‐onset dementia, epilepsy or tremor 21,40,44,57 .…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…occurring during febrile illness or other catabolic states) like acute or chronic onset of MD in infants, gait abnormalities or (truncal) muscular hypotonia. 5,45,[88][89][90][91][92][93][94][95][96][97] Individuals with late-onset form may present with unspecific neurologic signs like polyneuropathy, incontinence, headache, earlyonset dementia, epilepsy or tremor. 21,40,44,57 Neuroradiologic abnormalities occur frequently in all patients and are summarised in Table S3.…”
Section: Targeted Diagnostic Work-up Due To Suggestive Clinical Bioch...mentioning
confidence: 99%